Association of amyloid load uptake and cerebral blood flow in non‐Alzheimer's disease dementia and mild cognitive impairment: Neuroimaging / Normal brain aging. (7th December 2020) - Chau, Anson CM; Cheung, Eva YW; Shea, Yat Fung; Chiu, Patrick Ka‐Chun; Mak, Henry; Bao, Yiwen
Abstract: Background: Fibrillary beta amyloid deposits and cerebral hypoperfusion are upstream and downstream pathological features in demented individuals respectively. Asymptomatic amyloid plaque deposition begins and becomes saturated way before cerebral structural and metabolic changes in the course of Alzheimer's disease dementia, and their relationships been vigorously studied. However, the relationship of amyloid load and cerebral functions in non‐AD dementia is under‐investigated. This study aims to investigate the correlation between plaque deposition and cerebral blood flow (CBF) in non‐AD demented individuals. Method: Thirty‐three non‐AD demented subjects recruited for PET amyloid/MRI study in a University hospital. Each subject underwent a multiparametric MRI brain scanning which included 3D T1W and 2D pseudo‐continuous ASL sequence, and 18F‐Flutametamol Positron Emission Tomography Computed Tomography (PET‐CT). Standardized uptake value ratio (SUVR) of 18F‐flutametamol in eight bilateral cortical regions and absolute CBF of the same regions recorded for each subject. Partial correlation controlling for age between CBF and flutametamol uptake of each brain region computed. Result: Six non‐amnesic mild cognitive decline (MCI), 14 MCI with vascular pathologies and 13 vascular dementia had SUVR uptake ranged from 0.42 to 0.54, with the most deposition in the occipital, precuneus posterior cingulate (PCC), anterior cingulate, and the least in the prefrontal. Significant mild positive correlations (r=0.3) between SUVR uptake and CBF were found in occipital, anterior cingulate, sensorimotor and prefrontal. Significant moderate positive correlations (r=0.4) were found in temporal lateral and parietal. No significant correlation was found in PCC and temporal mesial. Conclusion: Increased amyloid deposition in non‐AD dementia and MCI has positive correlation with cerebral blood flow, possibly indicating a different pathophysiological mechanism from AD.